Wealth Management on the Macro Scale : Strategic Asset Allocation Within Sovereign Wealth Funds - White, Caroline (2020)
Macro wealth management, best observed in sovereign wealth funds (SWFs), has recently been of particular interest to the public in light of the present volatility in the global financial markets. This paper aims to address this interest by providing insight into the asset allocation strategies of SWFs with consideration to their source of wealth and investment mandate. It evaluates whether or not SWFs with a certain source of wealth and investment mandate follow an asset allocation strategy distinct from those with another source of wealth and investment mandate. To do so, a sample size of SWFs was chosen and grouped according to their source of wealth and investment mandate, with subsequent analysis following the analytical-synthetic methodology approach. The analysis revealed that source of wealth and investment mandate do correlate with divergent approaches to asset allocation, particularly in the class of alternative investments, in addition to activeness in portfolio companies, especially amongst oil-based SWFs. Therefore, a conclusion is reached that the strategic asset allocation of SWFs will vary based on the SWF’s source of wealth and investment mandate. The sample size used within this paper was small due to inconsistency in transparency amongst SWFs, therefore future research should be undertaken as SWFs become more transparent to evaluate the strength of this relationship between strategic asset allocation and source of wealth and investment mandate.